I diritti dell'infanzia a vent'anni dalla Convenzione: prospettive di ricerca per un bilancio storico - Emiliano Macinai (Firenze University Press, 2011)
A framework for the history of children's rights within a pedagogical perspective enables us to watch your child in a new light, that only in the twentieth century began to emerge slowly buy up to a final takeover at the end of the century: the child understood as legal person, an active subject of rights and equal relationships that link him to the adult. Much has been written about the historical milestones that have paved the ideal and material changes to the twentieth-century idea of childhood, up to the International Convention on the Rights of the Child.